Evaluating Global Cybersecurity Laws: Efectiveness of Legal Frameworks and Enforcement Mecanism in the Digital Age - Rusydi, Muhammad Taufik (Universitas Islam Negeri Walisongo Semarang, 2024)
This study examines the role of public-private partnerships (PPP) in enhancing cyber law enforcement across diverse legal systems. Employing a systematic literature review methodology, the research explores the effectiveness of collaborative efforts between the public and private sectors in addressing cyber threats. The findings indicate that PPP hold significant potential to bolster law enforcement through technological innovation and operational cooperation. Nevertheless, challenges such as transparency, trust deficits, and conflicting interests persist as critical obstacles to their success. The study recommends that policymakers strengthen legal frameworks, promote transparency, and foster capacity-building through joint training programs. Additionally, the research highlights gaps in the existing body of literature, emphasizing the necessity for more comprehensive empirical investigations to better understand and address the complexities of cyber law enforcement through PPP. Penelitian ini mengkaji peran kemitraan publik-swasta (public-private partnerships) dalam memperkuat penegakan hukum siber di berbagai sistem hukum. Dengan menggunakan metode tinjauan literatur, penelitian ini menganalisis efektivitas kolaborasi antara sektor publik dan swasta dalam mengatasi ancaman siber. Hasil penelitian menunjukkan bahwa PPP memiliki potensi besar untuk meningkatkan penegakan hukum melalui inovasi teknologi dan kerja sama operasional. Namun, tantangan seperti transparansi, defisit kepercayaan, dan perbedaan kepentingan tetap menjadi hambatan utama dalam keberhasilannya. Penelitian ini merekomendasikan agar pembuat kebijakan memperkuat kerangka hukum, mempromosikan transparansi, dan meningkatkan kapasitas melalui program pelatihan bersama. Selain itu, penelitian ini menyoroti keterbatasan dalam literatur yang ada dan menekankan pentingnya studi empiris yang lebih mendalam untuk memahami dan mengatasi kompleksitas penegakan hukum siber melalui PPP.